El desempeño del sistema de justicia civil italiano: una evaluación empírica - Caponi, Remo (Pontificia Universidad Católica del Perú, 2016)
The unreasonable length of Italian civil proceedings goes on filling pages of newspapers and magazines. According to some authoritative views, the inefficiency of the civil justice system helps explain why the Italian model legislation on civil proceedings, as well as its academic research, are not as influential on the European scene as they were in the past. It is interesting to note that an opposed thesis has pointed out that the Italian procedurallaw and recent researches in civil proceedings lack a clear, up-to-date, principle-oriented and comprehensive approach towards problems and challenges that contemporary civil justice systems face today. Such an outdated and overly complicated approach might contribute to the inefficiency of the Italian civiljustice system. The Italian Law Journal, which aims to both spread knowledge (and criticism) of the Italian legal system and foster international debate among lawyers of different traditions, may be an appropriate venue for deepening our understanding of the current performance of the Italian civil justice system. Itmay, in particular, assist in ascertaining the major causes of the inefficiencies, with a view to assessing (in a subsequent article) if the prevailing way of thinking of legal scholars may, in the end, exacerbate the relevant problems.

La longitud poco razonable de los procesos civiles italianos continúa llenando páginas de periódicos y revistas. De acuerdo con algunas opiniones autorizadas, la ineficiencia del sistema de justicia civil ayuda a explicar el motivo por el cual el modelo italiano de legislación en materia de procedimiento civil, así como su investigación académica, no sean tan influyentes en la escena europea como lo fueron en el pasado. Es interesante notar que una tesis opuesta ha señalado que el derecho procesal italiano y las investigaciones recientes sobre el proceso civil carecen de un enfoque claro, integral, actualizado y orientado por principios sobre los problemas y desafíos que el sistema de justicia civil afronta actualmente. Tal enfoque anticuado y demasiado complicado podría contribuir a la ineficiencia del sistema de justicia civil italiano. El Italian Law Journal, cuyo objetivo es la difusión de conocimiento (y crítica) del sistema legal italiano y la promoción del debate internacional entre abogados de distintas tradiciones, puede ser un modo apropiado para profundizar nuestra comprensión del desempeño actual del sistema de justicia civil italiano. Puede, en particular, ayudar a determinar las principales causas de las ineficiencias con el fin de evaluar (en un artículo posterior) si la forma predominante de pensamiento de los estudiosos del derecho posiblemente, al final, exacerba problemas relevantes.
The performance of Italian civil justice system: an empirical assessment
Keywords: Italian Civil Justice System; Civil Proceedings; Inefficiency; Undue Delay; Judges; Litigations; Cultural Mentality; Sistema de Justicia Civil Italiano; Procesos Civiles; Ineficiencia; Dilación Indebida; Jueces; Litigios; Mentalidad Cultural; https://purl.org/pe-repo/ocde/ford#5.05.00